Financing micro, small, and medium enterprises : an independent evaluation of IFC's experience with financial intermediaries in frontier countries - Carpio, Denis T.; International Finance Corporation; World Bank Independent Evaluation Group (International Finance Corporation, World Bank Group, 2008)
This study evaluates the effectiveness of IFC's strategic priority of private sector development in frontier countries (high-risk and/or low-income) by supporting micro, small, and medium enterprises (MSMEs) during fiscal years (FY)1994-2006. IFC has channeled its support to MSME's by: i) indirect financing through financial intermediaries, and ii) by indirect institution-building support via specialized regional small and medium enterprise (SME) development facilities. This evaluation analyzes IFC's development results and provides recommendations on how IFC's performance can be improved in this area going forward